Komunikasi Interpersonal dalam Pembelajaran Digital: Studi Kasus Live TikTok @broaal.english - Ismail Muslimin; Zulaikha; Didik Sugeng Widiarto (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2026)
This study analyzes interpersonal communication in digital learning via TikTok live streaming on the account @broaal.english, focusing on social presence and audience engagement. Using a qualitative case study method, data was collected from eight live sessions and included audience interactions and statistical engagement metrics. Findings revealed that the host, referred to as